Legal Jurisprudence on the Determination of Mandatory Maintenance and Madiyah Maintenance for Wives after Divorce ( Ecision Study Number 388/ Rev.G /2024/ PA.Prob ) - Jamilah Rizka; Sukiati, Sukiati; Mhd Yadi Harapan (SEAN Institute, 2025)
This paper explores the legal jurisprudence regarding livelihood iddah (obligatory maintenance during the waiting period) and livelihood madīyah (past maintenance) for ex-wives following divorce, through the lens of Decision Number 388/ Pdt.G /2024/ PA.Prob . The study is grounded in the urgent need for legal protection of women, particularly those who face economic vulnerability after divorce, by ensuring their right to financial support from former husbands. The research aims to analyze the judge's legal reasoning in awarding these two forms of maintenance, as well as to assess how the decision embodies substantive justice and aligns with both Islamic law and Indonesia's positive legal system. Utilizing a normative juridical approach and qualitative descriptive analysis, the study draws from document analysis and legal literature. The findings indicate that the judge's decision was based on considerations of Sharia principles, statutory regulations, the husband's financial capacity, and the overarching aim of justice and protection of women's rights. However, deficiencies were identified in the form of ambiguous criteria for the amount of maintenance awarded and insufficient elaboration on the evidence supporting livelihood madīyah . Despite these limitations, the decision marks a significant contribution to the development of jurisprudence that prioritizes justice and safeguards for women post-divorce .